2018
DOI: 10.1002/pon.4845
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities are associated with poorer quality of life and functioning and worse symptoms in the 5 years following colorectal cancer surgery: Results from the ColoREctal Well‐being (CREW) cohort study

Abstract: ObjectiveMore people are living with the consequences of cancer and comorbidity. We describe frequencies of comorbidities in a colorectal cancer cohort and associations with health and well‐being outcomes up to 5 years following surgery.MethodsProspective cohort study of 872 colorectal cancer patients recruited 2010 to 2012 from 29 UK centres, awaiting curative intent surgery. Questionnaires administered at baseline (pre‐surgery), 3, 9, 15, 24 months, and annually up to 5 years. Comorbidities (and whether they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 35 publications
6
29
1
Order By: Relevance
“…In line with our findings, various studies have found that, in patients with endometrial cancer or different cancer types, independent of age, comorbidity was associated with poorer HRQoL at baseline or HRQoL deterioration at follow-up [11][12][13]32]. One previous study from our group reported on the association between changes in HRQoL and clinical and sociodemographic characteristics of patients included in the Rogy Care trial and also described the association between cumulative comorbidity burden and poorer HRQoL [12].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In line with our findings, various studies have found that, in patients with endometrial cancer or different cancer types, independent of age, comorbidity was associated with poorer HRQoL at baseline or HRQoL deterioration at follow-up [11][12][13]32]. One previous study from our group reported on the association between changes in HRQoL and clinical and sociodemographic characteristics of patients included in the Rogy Care trial and also described the association between cumulative comorbidity burden and poorer HRQoL [12].…”
Section: Discussionsupporting
confidence: 90%
“…Various prior studies have found that age above 60 and comorbidity were independently associated with treatment-related morbidity and poorer survival [6][7][8][9][10]. Perhaps more importantly, both factors may also impact health-related quality of life (HRQoL) [11][12][13][14][15]. This outcome is of particular interest to patients suffering from cancers with a relatively good prognosis such as endometrial cancer and to older adults with cancer, who often give preference to maintenance or improvement of HRQoL rather than a small increase in survival [6,16].…”
Section: Introductionmentioning
confidence: 99%
“…Whilst having comorbidities per se may not be amenable to change, the way comorbidities are managed could be. Our previous work has shown that it is the impact of comorbidities on daily life which influences QOL [44], and personalised assessment and management for people with comorbidities may improve outcomes.…”
Section: Plos Onementioning
confidence: 99%
“…Furthermore, the majority of people LWBC are living with at least one other long-term chronic condition (e.g. hypertension, obesity, mental health conditions) [17, 18]. The shared risk factors between cancer and heart disease, and toxicity of cancer treatment, can also leave people LWBC at increased risk of cardiovascular disease [19, 20].…”
Section: Introductionmentioning
confidence: 99%